Compression Analysis of Hollow Cylinder Basalt Continuous Filament Epoxy Composite Filled with Shape Memory Wire - Mohammad Reza Khalili; Morteza Rajabpour; Mohammad Reza Jafarinezhad; Roham Maher (Mechanics of Advanced Composite Structures, 2017)
This paper presents an experimental investigation into the compression behavior of shape memory alloy hybrid composites (SMAHC) subjected to quasi-static loading taking into account of rotation effects of shape memory wire in basalt continuous filament (BCF) direct roving epoxy composite. Two types of specimen prepared, the BCF direct roving reinforced epoxy composite filled with shape memory wire and BCF direct roving reinforced epoxy composite without shape memory wire and compression strengths of two specimens per type are analyzed. Specimens were prepared by hand layup at room temperature for curing. For composites specimen four layer BCF direct roving reinforced epoxy composite prepared. The effect of shape memory wire on the maximum load bearing capacity of resultant specimens after quasi static damage was experimentally investigated. Results of compression test for two specimens per type of BCF and SMAHC showed that composite specimens with four layer BCF direct roving reinforced epoxy composite has higher load than SMAHC specimens with rotate wire between second and third layer. It may for weak interface between shape memory wire and matrix due to the discrepancy in compatibility of materials.